PopulasiWerengHijau(Nephotettixspp.)PadaTanamanPadiSawah di KecamatanDumogaTimurKabupatenBolaangMongondow - Christman F. Lepa; Elisabeth R. M. Meray; Jusuf Manueke (Universitas Sam Ratulangi, 2017)
ABSTRACTThe study aimed to find out the population of green leafhoppers Nepotettix spp to rice plant. The study was conducted in Mogoyunggung, Tonom, and Imandi villages, east Dumoga district, Bolaang Mongondow regency. The study was held from April until june 2017. The study used servey method in these three villages. The study surveyed a field of 500 square meters from each village. The sampling used diagonal slice method by determining five sub-plots in each sampling area.The result showed that the average population of green leafhoppers Nepotettix spp on the first observation reached the highest number of 8,33, meanwhile on the third observation the lowest number showed 4,0, on the second observation is 4,13.Keywords : The population of green leafhoppers ; Nephotettix spp: Rice plant